Environmental and Economic Analysis of Selected Pavement Preservation Treatments - Kelvin Zulu; Rajendra P. Singh; Farai Ada Shaba (Salehan Institute of Higher Education, 2020)
Pavements are one of the highest assets and represent massive investment. The need to design and provide a sustainable maintenance service is becoming a priority and this comes mutually with the intentions to reduce impacts caused by maintenance treatments to the environment. This paper through a case study presents a Life Cycle Cost and Assessment technique during a 30 year analysis period to measure the cost effectiveness, embodied energy and carbon emissions of selected preservation treatments. These treatments can either be applied separately or in combination during the preventive maintenance of road pavements. This study entails three life cycle phases of material extraction and production, transportation and construction of maintenance activities. Through a literature review, raw materials energy and emission inventory data was averaged followed by the analysis of the equipment involved by using the specific fuel consumption to calculate the energy and emissions spent by the machine and finally the selected treatment energy and emissions was computed. Results show that preservation treatments can have an LCC of 30-40 % and embodied energy and carbon emission of 3-6 times lower than the traditional approach. This study bridges gaps in literature on integrated evaluation of environmental and economic aspects of preservation treatments.